Turism, Mobilities and Responsibility in the ‘New Europe” - Hall, Derek (Turyzm/Tourism, 2007)
This paper highlights issues relating to the relationship between tourism and mobility evident in the newly enlarged European Union (EU). This is set within a context of policy contradictions linking tourism, mobilities and climate change. It is suggested that there is an urgent requirement to critically evaluate the concept and practice of ‘responsibility' in European tourism.